2009
DOI: 10.1016/j.jaad.2008.10.062
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence of adult-onset psoriasis over three decades: A population-based study

Abstract: BACKGROUND-Incidence studies of psoriasis are rare, mainly due to lack of established epidemiological criteria and the variable disease course. The objective of this study is to determine time trends in incidence and survival of psoriasis patients over three decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
207
5
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(233 citation statements)
references
References 38 publications
14
207
5
7
Order By: Relevance
“…A similar study in the capital city showed the prevalence rate of 3.6%. 10 Psoriasis was found to be more common in male (53.75%) in our study with M:F = 1.16. This finding is supported by various other studies.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…A similar study in the capital city showed the prevalence rate of 3.6%. 10 Psoriasis was found to be more common in male (53.75%) in our study with M:F = 1.16. This finding is supported by various other studies.…”
Section: Discussionsupporting
confidence: 47%
“…This finding is supported by various other studies. [10][11][12] Some studies show that this disease is equal or more common in female. 13 This may be a likely scenario even in our place due to limited access to health care facilities in case of female.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Epidemiologic studies have shown that psoriasis is an increasingly common disease, which has almost doubled in annual incidence since the 1970s. 18 We found that the prevalence of psoriasis research initially showed a variable course, with an eventual downward trend around 1990, but has seen a steady increase since 2000. This may be largely attributable to the development of tumor necrosis factor inhibitor therapy around this time, which has proved to be very successful in the treatment of psoriasis.…”
Section: Discussionmentioning
confidence: 73%
“…Stwierdzono, że u kobiet w 5. i 6. dekadzie życia wzrasta znacząco zachorowalność na łuszczycę, osiąga-jąc wskaźnik 90,7 na 100 000 [6]. Należałoby wiązać te zmiany z menopauzą oraz okresem pomenopauzalnym.…”
Section: Wstępunclassified